Cosmeceutical benefits of stingless bee honey - Hazrina Hadi; Nuraqilah Zulkifli (IIUM Press, International Islamic University Malaysia, 2023)
There were about 500 stingless bee species that had been reported in Afrotropical, Indo-Australian and Neotropical provinces with the highest diversity species originating in the Neotropical. In Malaysia, there are more than 38 species and around 33 species were reported in Peninsular Malaysia. Due to its high nutritious and medicinal values, recently, stingless bee honey has been highly demanded by the food, pharmaceutical and even cosmetic industries. Thus, this paper describes the cosmeceutical potential of stingless bee honey as an antiacne, skin moisturizing and anti-hypertrophic scar agent. Stingless bee honey can treat acne by reducing inflammation and irritation during acne formation due to its high flavonoid and phenolic compounds. Besides, stingless bee honey also possesses antibacterial activity due to its acidity, osmolarity and hydrogen peroxide content which is unfavourable for P.acne growth. It functions as a natural humectant due to its ability to attract water from the dermis and deeper epidermis to the epidermis and its high water-binding capacity. Stingless bee honey also can reduce scar formation by improving the wound healing process. This is because it can possess both pro-inflammatory and anti-inflammatory properties in which it triggers the production of the pro-inflammatory cytokines to initiate the inflammation and inhibit the production of the pro-inflammatory cytokines when inflammation is in progress to avoid prolonged inflammation. Also, stingless bee honey can stimulate skin reepithelialization and wound contraction. These will reduce the damaged tissue that needs to be repaired and eventually minimize the scarring area. Hence, due to all of these benefits, further research can be done to study the action, use and effectiveness of stingless bee honey in cosmetic applications.